The Rickettsial Ankyrin Repeat Protein 2 Is a Type IV Secreted Effector That Associates with the Endoplasmic Reticulum - Stephanie S. Lehman (American Society for Microbiology, 2018)
ABSTRACT Strains of Rickettsia rickettsii, the tick-borne agent of Rocky Mountain spotted fever, vary considerably in virulence. Genomic comparisons of R. rickettsii strains have identified a relatively small number of genes divergent in an avirulent strain. Among these is one annotated as Rickettsia ankyrin repeat protein 2 (RARP-2). Homologs of RARP-2 are present in all strains of R. rickettsii, but the protein in the avirulent strain Iowa contains a large internal deletion relative to the virulent Sheila Smith strain. RARP-2 is secreted in a type IV secretion system-dependent manner and exposed to the host cell cytosol. RARP-2 of Sheila Smith colocalizes with multilamellar membranous structures bearing markers of the endoplasmic reticulum (ER), whereas the Iowa protein shows no colocalization with host cell organelles and evidence of proteolytic degradation is detected. Overexpression of Sheila Smith RARP-2 in R. rickettsii Iowa converts this avirulent strain’s typically nonlytic or opaque plaque type to a lytic plaque phenotype similar to that of the virulent Sheila Smith strain. Mutation of a predicted proteolytic active site of Sheila Smith RARP-2 abolished the lytic plaque phenotype but did not eliminate association with host membrane. RARP-2 is thus a type IV secreted effector and released from the rickettsiae into the host cytosol to modulate host processes during infection. Overexpression of Sheila Smith RARP-2 did not, however, restore the virulence of the Iowa strain in a guinea pig model, likely due to the multifactorial nature of rickettsial virulence. IMPORTANCE Members of the genus Rickettsia are obligate intracellular bacteria that exhibit a range of virulence from harmless endosymbionts of arthropods to the etiologic agents of severe disease. Despite the growing number of available genomes, little is known regarding virulence determinants of rickettsiae. Here, we have characterized an ankyrin repeat-containing protein, RARP-2, which differs between a highly virulent and an avirulent strain of R. rickettsii, the agent of Rocky Mountain spotted fever. RARP-2 is secreted by a type IV secretion system into the cytosol of the host cell, where it interacts with and manipulates the structure of the endoplasmic reticulum. RARP-2 from the avirulent strain is truncated by the loss of seven of 10 ankyrin repeat units but, although secreted, fails to alter ER structure. Recognition of those rickettsial factors associated with virulence will facilitate understanding of regional and strain-specific variation in severity of disease.